2021
DOI: 10.3389/fphar.2021.639458
|View full text |Cite
|
Sign up to set email alerts
|

The Protection of Crocin Against Ulcerative Colitis and Colorectal Cancer via Suppression of NF-κB-Mediated Inflammation

Abstract: Background: In China, the incidence of ulcerative colitis (UC) is increasing every year, but the etiology of UC remains unclear. UC is known to increase the risk of colorectal cancer (CRC). The aim of this study was to investigate the protective effects of crocin against UC and CRC in mouse models.Methods: Crocin was used to treat the dextran sodium sulfate (DSS)-induced UC mice for 3 weeks, and ApcMinC/Gpt mice with colorectal cancer for 8 weeks. Proteomics screening was used to detect changes in the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…One possible explanation is that crocin has been reported to have multiple acting targets including anti-inflammation, BDNF, and apoptosis etc. ( Hosseinzadeh and Talebzadeh, 2005 ; He et al, 2016 ; Mazumder et al, 2017 ; Rana and Musto, 2018 ; Teng et al, 2021 ). Due to the multiple targets, different treatment doses may activate different targets and pathways, which may cause the anti-epileptic effect of crocin lacks significant dose-dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that crocin has been reported to have multiple acting targets including anti-inflammation, BDNF, and apoptosis etc. ( Hosseinzadeh and Talebzadeh, 2005 ; He et al, 2016 ; Mazumder et al, 2017 ; Rana and Musto, 2018 ; Teng et al, 2021 ). Due to the multiple targets, different treatment doses may activate different targets and pathways, which may cause the anti-epileptic effect of crocin lacks significant dose-dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Crocin is considered as one of the main effective components of saffron with a low toxicity ( Bostan et al, 2017 ). Extensive preclinical and clinical studies about its traditional use have been reported, such as anti-inflammation ( Teng et al, 2021 ), anti-tumor ( Mousavi et al, 2009 ), sedation and hypnosis ( Masaki et al, 2012 ), anti-depression ( Amin et al, 2015 ), anti-anxiety ( Pitsikas et al, 2008 ) and anti-Parkinson’s disease ( Rao et al, 2016 ). Several papers also reported its anti-epileptic activity in experimental epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of saffron may be achieved by the virtue of its antioxidant property. NF-κB, being a redox-sensitive transcription factor, is activated by various inflammatory insults and translocate to the nucleus to induce proinflammatory cytokines during inflammation [ 16 , 17 ]. Saffron pre-treatment inhibited the nuclear translocation of p65 NF-κB in mice colonic tissue samples, which corresponds to inhibition of the secretion of IL-6, IL-1β, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Saffron, by virtue of its potent antioxidant property, showed a significant decrease in lipoprotein oxidation susceptibility (LOS) in human subjects and was evaluated as a promising anti-obesity drug [ 16 ]. Crocin, a biologically active carotenoid constituent of saffron, was demonstrated to protect against DSS-induced colitis in C57BL/6 J mice and suppressed tumor growth in ApcMinC/Gpt mice by suppressing NF-κB-mediated inflammation [ 17 ]. NF-κB, an oxidative stress sensitive transcription factor, is associated with tissue induction of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease activity index (dai) is a comprehensive score of weight loss, stool consistency and rectal bleeding that is used extensively to evaluate the clinical progress of patients with colitis (21,22). dai values were calculated according to a previously described method (23).…”
Section: Animal Experimentsmentioning
confidence: 99%